Age-Associated Changes in Proximal Femur Morphology Affect Femoral Component Sizing in Cementless Hip Arthroplasty - Hidde D. Veldman MD; Tim A. E. J. Boymans MD, PhD; Liza N. van Steenbergen PhD; Ide C. Heyligers MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation, 2022)
Background In cementless hip arthroplasty, the femoral component should obtain firm fixation within the endosteal bone and achieve adequate reconstruction of hip joint biomechanics simultaneously. Previous anatomical studies described age-related changes of the proximal femoral canal, such as canal widening, which theoretically necessitates the use of larger stem sizes in elderly patients. This study examines a potential association between patients’ age at surgery and the implant size of a cementless femoral component. Material and methods A total of 13,423 primary hip arthroplasties with a single cementless stem registered in the Dutch Arthroplasty Register (LROI) were included. Patient characteristics (ie patients’ age, sex, height and weight at time of surgery) and femoral component size were derived. A one-way ANCOVA was used to compare the mean stem size between age groups, and multivariable linear regression analysis was used in order to investigate to which extent ageing impacted stem size. Results Each subsequent age- group (ten-year intervals) had a significantly larger mean stem size than the prior age- group. Multivariable linear regression analysis revealed that age is positively correlated with stem size and that this correlation is more prominent in females than in males (beta = .046, P < .001 and beta = .028, P < .001 respectively). Interpretation Implant size is positively correlated with age, in particular in females and independently from investigated anthropometric characteristics. The present study endorses that the femoral canal morphology is related to patients’ characteristics such as age and sex. The morphology will subsequently influence implant sizing and therefore may have biomechanical and clinical implications.